Impact of multimodal intraoperative neurophysiological monitoring of the spinal cord during spine and spinal cord surgeries - Walaa Elwakil; Mohamed Imam; Marwa Hassan; Waleed Elsaadany; Omnia Gaber (Egyptian Rheumatology and Rehabilitation, 2023)
Abstract Background There is growing evidence of the valuable role of multimodal intraoperative neurophysiological monitoring (IONM) during spine and spinal cord surgeries, as it provides an opportunity to recognize functional changes of the neural elements, usually in the reversible stage, during complex surgical manipulations. Therefore, it may reduce the risk of postoperative neurological dysfunction and improve functional outcomes. The aim of the current study was to evaluate the efficacy of multimodal IONM for preventing and predicting iatrogenic neurological dysfunction during spinal cord and spine surgeries. Results Significant alerts had occurred in 9 out of 24 patients; however, all the changes were reversible and did not contribute to postoperative clinical deterioration. Only one case got worsened in the early postoperative follow-up period, with stable intraoperative monitoring. Conclusion Intraoperative monitoring is a valuable tool in spine and spinal cord surgeries. Combined transcranial motor-evoked potential (TcMEP), somatosensory-evoked potential (SSEP), and spontaneous electromyography (EMG) monitoring may prevent permanent motor deficit and enhance the postoperative outcomes.